Low-Carbon and Green Materials in Construction: Latest Advances and Prospects - Jie Xiao; Jun Shuai; Weiqing Deng; Lingfei Liu; Pujin Wang; Long Li (Buildings)
In recent years, with the acceleration of urbanization and the continuous expansion of construction at all scales, the safety, durability, and sustainability of building structures have come to face multiple challenges [...]